Pragmatic Analysis of Assumption Found in the “Sang Pemimpi” Film - Atalisi Zalukhu; Eva Febriana C Gulo (Journal of Language Education (JoLE), 2024)
The purpose of this research is to determine the type of Assumption and the dominant of Assumption contained in Sang Pemimpi film. This research uses a qualitative descriptive method that aims to describe the data with the. The data of this research is Sang Pemimpi Film. The data in this study were obtained from conversations between characters in the Film The source of research data comes from this film script. Data collection was conducted using observation, taking notes, and reduction. The implied meaning of each type of Assumption is determined based on the context of the situation. The researcher found 42 utterances in Sang Pemimpi's film with details: existential Assumption 11 (26%), factive Assumption 9 (21%), structural Assumption 9(21%), counter-factual Assumption 7 (17%), lexical Assumption 4 (10%) and non-factive Assumption 2 (5%). Based on the results of this research, six types of Assumptions and Assumptions are most often found in this film. Assumption can be informally defined as an inference or a proposition. Its truth is taken for granted in the utterance of sentences. The listener can capture other information apart from the interpretation.